Caracterización de la producción de Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs y Urochloa decumbens (Stapf) R.D. Webster en pastoreo con caprino - Miguel Ángel Macay-Anchundia (Pastos y Forrajes)
Objective: To characterize the production per area unit of Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs and Urochloa decumbens (Stapf) R.D. Webster in a rational Voisin grazing system with goats in Manabí, Ecuador. Materials and Methods: The total study area was 0,22 ha, divided into eleven quarters of each pasture, with a stocking rate of 12 adult goats, water ad libitum and supplementation with nutritional blocks. The treatments were: T1) M. maximus and T2) U. decumbens. Data were analyzed with general linear and mixed models. A randomized complete block design was applied, with a significance level of 0,05 (Tukey) and the R program was used. During the dry season of 2022, green forage production/ha, days of recovery and remnant were measured. Results: In green forage production/ha there were differences (p= 0,0068) and M. maximus pasture obtained the best yields (11 800 kg). This same grass showed the shortest resting time (56 days). Differences (p= 0,0036) were recorded for remnant. The highest average was reached in M. maximus (3 700 kg). Conclusions: M. maximus and U. decumbens showed high green forage production per area unit in the rational Voisin grazing system with goats, although M. maximus obtained higher yields, better recovery and higher remnant during the evaluation